A new, riparian, species of Allobates Zimmermann and Zimmermann, 1988 (Anura: Aromobatidae) from southwestern Amazonia - Melo-Sampaio, Paulo Roberto; de Souza, Moisés Barbosa; Peloso, Pedro Luiz Vieira (Zootaxa, 2013)
We describe Allobates flaviventris sp. nov., a medium-sized (SVL 16.7–19.7 mm in males; 19.3–21.1 mm in females) aromobatid frog with Finger III not swollen in adult males from eastern state of Acre, Brazil. It inhabits open forests with bamboo, usually along small streams and rivers. it has golden-yellow belly and a unique advertisement call as a distinctive character. Notes on natural history are also provided.